The Effect of Hematocrit and Nanoparticles Diameter on Hemodynamic Parameters and Drug Delivery in Abdominal Aortic Aneurysm with Consideration of Blood Pulsatile Flow. (October 2020) - Jafarzadeh, Sina; Nasiri Sadr, Arsalan; Kaffash, Ehsan; Goudarzi, Sahar; Golab, Ehsan; Karimipour, Arash
Highlights: The effect of hematocrit and nanoparticles diameter on wall shear stress flow pattern and drug persistence in abdominal aortic aneurysm Blood enters the artery as a pulsatile flow Wall shear stress intensifies by increasing hematocrit In low hematocrit, maximum accumulation of drug occurs on dilatation wall Abstract: Background and Objective: The present article has simulated to investigate the efficient hemodynamic parameters, the drug persistence, and drug distribution on an abdominal aortic aneurysm. Methods: Blood as a non-Newtonian fluid enters the artery acting as a real pulse waveform; its behavior is dependent on hematocrit and strain rate. In this simulation of computational fluid dynamic, magnetic nanoparticles of iron oxide which were in advance coated with the drug, are injected into the artery during a cardiac cycle. A two-phase model was applied to investigate the distribution of these carriers. Results: The results are presented for different hematocrits and the nanoparticle diameter. It is observed that hematocrit significantly affects drug persistence, so that lower hematocrit incites more accumulation of the drug in the dilatation part of the artery. The better drug accumulation is noticed, at the higher wall shear stress. Although no considerable impact on the flow pattern and wall shear stress was found with various nanoparticle diameters, the smaller size of the nanoparticles results in a greater amount of drug augmentation in the aneurysm wall output. Conclusions: At the higher hematocrit levels, the blood resistance to drug delivery increases throughout the artery. Also, the drug accumulates less on the aneurysm wall and stays longer on the aneurysm wall. On the contrary, the drug accumulates more by decreasing hematocrit level and stays shorter on the aneurysm wall. Moreover, the maximum drug concentration is observed at the lowest hematocrit level and nanoparticle diameter; also, the diameter of nanoparticles imposes no significant effect on the vorticity and wall shear stress. It is seen that the increment of the hematocrit level reduces the strength of vorticity and increases the amount of wall shear stress in the dilatation segment of the artery. The shear stress at three points of the dilatation wall is extreme, where the maximum density of nanoparticles occurs.